Core Competencies of School Administrators in 21st Century affecting Professional Learning Community in Primary Schools under Krabi Primary Educational Service Area Office - สิทธิฤาชัย, วันทนา; ชูกำเนิด, วรลักษณ์ (วารสารศึกษาศาสตร์ มหาวิทยาลัยสงขลานครินทร์ วิทยาเขตปัตตานี, 2020)
The purposes of the research were 1) to study the level of core competencies of school administrators in 21st century 2) to study the level of professional learning community in primary schools and 3) to find the predicted variables used to predict the professional learning community in primary schools under Krabi Educational Service Area Office. The sample of the research was 148 schools; the informants were an educational administrator and a teacher who was the head of academic affair from the schools. The instrument for collecting data was a Likert’s rating scale questionnaire about core competencies of school administrators in 21st century (the value of reliability range from .689-.857) and professional learning community (the value of reliability range from .740-.833). The statistics were based on average, standard deviation, Correlation coefficient, and stepwise multiple regression analysis. The results were as follow: 1) The overall of core competencies of school administrators in 21st century under Krabi Educational Service Area Of - fice was at the highest level. 2) The overall of professional learning community in the schools under Krabi Educational Service Area Office was at the highest level. 3) Core competencies of school administrators in 21st century such as collective learning and team working competency, self - directed professional development competency and also integrity and accountability competency can affect to and can be predicted professional learning community in the schools with statistically significant at .01 level; the multiple correlation coefficient (R) was .795 And the predictive power was at 63.2 percent (R2 =.632).